Underestimation of the expression of cellular prion protein on human red blood cells - Panigaj, Martin; Brouckova, Adela; Glierova, Hana; Dvorakova, Eva; Simak, Jan; Vostal, Jaroslav G; Holada, Karel (Transfusion, 2011)
BACKGROUND: Recent transmissions of variant Creutzfeldt-Jakob disease by blood transfusion emphasize the need for the development of prion screening tests. The detection of prions in blood is complicated by the presence of poorly characterized cellular prion protein (PrP(C) ) in both plasma and blood cells. According to published studies, most of PrP(C) in blood cells resides in platelets (PLTs) and white blood cells. STUDY DESIGN AND METHODS: To clarify conflicting reports about the quantity of PrP(C) associated with human red blood cells (RBCs), quantitative flow cytometry, Western blot (WB), and enzyme-linked immunosorbent assay (ELISA) were used to measure protein levels in healthy donors. RESULTS: RBCs expressed 290 ± 140 molecules of PrP(C) per cell, assuming equimolar binding of monoclonal antibody (MoAb) 6H4 to PrP(C). Binding of alternate PrP(C) MoAbs, FH11 and 3F4, was substantially lower. WB estimated the level of PrP(C) per cell on RBCs to be just four times lower than in PLTs. A similar level of PrP(C) was detected using ELISA. The weak binding of commonly used MoAb 3F4 was not caused by PrP(C) conformation, truncation, or glycosylation, suggesting a covalent modification, likely glycation, of the 3F4 epitope. CONCLUSIONS: Taken together, human RBCs express low but significant amounts of PrP(C) /cell, which makes them, due to high RBC numbers, major contributors to the pool of cell-associated PrP(C) in blood. Previous reports utilizing MoAb 3F4 may have underestimated the amount of PrP(C) in RBCs. Likewise, screening tests for the presence of the abnormal prion protein in blood may be difficult if the abnormal protein is modified similar to RBC PrP(C).
Keywords: Epitopes; Humans; Erythrocytes; Antibodies, Monoclonal; Blotting, Western; ELISA; Erythrocyte Membrane; lidé; Enzyme-Linked Immunosorbent Assay; Transfusion Reaction; PrPC proteiny; Creutzfeldt-Jakob Syndrome; glykosylace; Flow Cytometry; potransfuzní reakce; erytrocytární membrána; erytrocyty; Mass Screening; monoklonální protilátky; Creutzfeldtova-Jakobova nemoc; průtoková cytometrie; plošný screening; western blotting; epitopy; Glycosylation; PrPC Proteins